2001
DOI: 10.1023/a:1011187413930
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The complete nucleotide sequence including precise 5'- and 3'-terminal non-coding regions (NCRs) of the attenuated lapinized Chinese strain (HCLV) of Classical Swine Fever Virus (CSFV) was determined from overlapping cDNA clones constructed by separated RT-PCR and rapid amplification of cDNA ends (RACE) methods. The genomic RNA of the HCLV strain consists of 12.310 nucleotides (nts) including 374 nts and 242nts in the 5'- and 3'-NCRs, respectively. It contains one large open reading frame (ORF) encoding a poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…The highly virulent CSFV strain Margarita, likely the parental strain of the PdR virus (9), also carries the standard 5 uridines at this position. However, a similar 6-to 32-nucleotide-long uridine-rich insertion was found in the 3= UTR of several attenuated CSF vaccine virus strains, but this sequence was located approximately 90 nucleotides upstream of the PdR poly-U insertion (10,11). Previous studies showed that the 3= UTR of flaviviruses are implicated in virus replication (12,13).…”
mentioning
confidence: 79%
“…The highly virulent CSFV strain Margarita, likely the parental strain of the PdR virus (9), also carries the standard 5 uridines at this position. However, a similar 6-to 32-nucleotide-long uridine-rich insertion was found in the 3= UTR of several attenuated CSF vaccine virus strains, but this sequence was located approximately 90 nucleotides upstream of the PdR poly-U insertion (10,11). Previous studies showed that the 3= UTR of flaviviruses are implicated in virus replication (12,13).…”
mentioning
confidence: 79%
“…Three complete genomes of CSFV were previously sequenced by our laboratory (AF407339, AF091507, and AF092448) [18,19]. The other available complete CDS of CSFV were downloaded from GenBank in March 2008 and sequences with [99% sequence identities were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The other available complete CDS of CSFV were downloaded from GenBank in March 2008 and sequences with [99% sequence identities were excluded. A total of 35 CSFV genomes [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] representing 6 subgenotypes (1.1, 1.2, 2.1, 2.2, 2.3, and 3.4) and all 3 kinds of virulence (highly virulent strains, moderated virulent strains, and avirulent strains) were used in this study. The genotyping of 35 CSFV genomes was performed using the CSFV sequence database (http://viro08.tiho-hannover.…”
Section: Methodsmentioning
confidence: 99%
“…Although those mutations in E2 of Thiverval are not crucial mutations in virulence as that found in Brescia, they may cooperatively affect virulence of CSFV Thiverval strain. A 12-14 nucleotide (nt) T-rich insertion in the 3 0 -UTR can be found in most attenuated vaccine strains of classical swine fever, such as HCLV, C-strain, Porcivac, Ravoc, and Russian LK [13,14,34]. In this work, we found a significant difference among the 3 0 -UTR nucleotide sequences of Alfort A19, Alfort/187, and Thiverval vaccine strains.…”
Section: Discussionmentioning
confidence: 59%
“…The complete viral genomes of HCLV and GPE -vaccine strains were sequenced [12][13][14]. Understanding the genome sequences of these CSFV strains provides insight into the pathogenicity and the attenuation of the viruses.…”
Section: Introductionmentioning
confidence: 99%